Pengaruh Self Efficacy, Kompetensi dan Pengembangan Karir Terhadap Kinerja Guru di Sekolah Menengah Pertama Negeri 3 Sidoharjo - Rizvi Aulia Dewi Utami; Asih Handayani (Indo Publishing, 2025)
This study aims to analyze the influence of self-efficacy, competence, and career development on teacher performance at SMP Negeri 3 Sidoharjo. The research background shows that all teachers (100%) have